Wake vortices and tropical cyclogenesis downstream of Sumatra over the Indian Ocean - Fine, Caitlin Marie, author; Johnson, Richard H., advisor; Schubert, Wayne H., committee member; Kirby, Michael J., committee member (Colorado State University. Libraries, 2015)
A myriad of processes acting singly or in concert may contribute to tropical cyclogenesis, including convectively coupled waves, breakdown of the inter-tropical convergence zone (ITCZ), or upper-level troughs. This thesis investigates the role that topographic effects from the island of Sumatra may play in initiating tropical cyclogenesis (TC genesis) in the eastern Indian Ocean. If easterly flow is split by the mountains of Sumatra, counter-rotating lee vortices may form downstream. Because Sumatra straddles the equator, though the wake vortices rotate in opposite directions, they will both be cyclonic when winds are easterly upon Sumatra, and may intensify further into tropical cyclones. The phenomenon of cross-equatorial cyclone pairs, or "twin" tropical cyclones, in the Indian Ocean originating from Sumatra was first noted by Kuettner (1989). TC genesis appears to be particularly favored during the pre-onset phase of the Madden Julian Oscillation (MJO), when easterly flow encroaches upon Sumatra and the resulting cyclonic wake vortices encounter convectively coupled waves and enhanced moisture associated with the MJO in the Indian Ocean. Operational analysis data from the Year of Tropical Convection (YOTC) and Dynamics of the Madden Julian Oscillation (DYNAMO) campaigns were used to evaluate the impacts of Sumatra's topography upon the flow. The YOTC data encompass two years, from May 2008 to April 2010, while the special observing period of DYNAMO was conducted from October to December 2011. This research also presents three case studies of twin tropical cyclones west of Sumatra in the Indian Ocean, which were all determined to originate from Sumatran wake vortices and occurred between October and December of 2008, 2009, and 2011. Multiple cyclonic wake vortices and vorticity streamers were observed downstream of Sumatra during periods of easterly flow, most frequently between October and December. Froude numbers calculated for the region upstream of Sumatra with regard to easterly flow between October and December favored flow blocking and splitting, more so for Sumatra's northern tip due to the higher terrain there. Correlations between zonal wind and relative vorticity are more significant near Sumatra's northern tip than near and downstream of the island's southern tip. Cyclonic vorticity was maximized at the level of Sumatra's topography for most easterly wind days west of both the north and south ends of the island, suggesting that topography was contributing to vorticity generation. Thirteen tropical cyclones in the Indian Ocean during the YOTC and DYNAMO campaigns were determined to develop from cyclonic wake vortices downstream of Sumatra, including three tropical cyclone pairs. Over 75% of these tropical cyclones formed between October and December. In four cases, wake vortices were generated by anomalously easterly low-level flow that preceded the active phase of the Madden Julian Oscillation. These vortices proceeded to encounter the MJO convective envelope, which is frequently accompanied by convectively coupled waves and may have altered the environment to be more moist and favorable for tropical cyclogenesis. In many cases, equatorial westerly winds, which may have been related to westerly wind bursts from the MJO or to convectively coupled equatorial Rossby waves, intensified low-level cyclonic circulations. It is suggested that diabatic heating in the vicinity of twin tropical cyclones may disturb the atmosphere enough to invigorate extant convectively coupled Kelvin waves, or contribute to the formation of a Kelvin wave. The research presented herein describes the interaction of the flow with steep topography on Sumatra and its role in tropical cyclogenesis over the Indian Ocean, a mechanism for TC genesis that has heretofore received little attention.
Keywords: orographic effects on flow; tropical cyclogenesis; wake vortex; Sumatra; flow blocking; tropical cyclone